2005
DOI: 10.1071/fp04068
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to downy mildew in pearl millet is associated with increased phenylalanine ammonia lyase activity

Abstract: Phenylalanine ammonia lyase (PAL) activity was studied in pearl millet cultivars with different levels of resistance to the downy mildew disease caused by Sclerospora graminicola, an important oomycete pathogen. PAL activity was elevated in resistant host cultivar and decreased in susceptible cultivars following downy mildew pathogen infection. The enzyme activation varied between cultivars and was correlated with the degree of resistance to downy mildew disease. The induction of PAL as a response to pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 39 publications
4
31
0
Order By: Relevance
“…The homogenate was centrifuged at 20,000 g for 20 min at 48C in a refrigerated high-speed centrifuge (Hitachi, Japan). PAL activity in the supernatant of the cell free extracts was assayed as described by Geetha et al (2005). The reaction mixture (3 ml) consisted of 50 mM L-phenylalanine in 100 mM sodium borate buffer (pH 8.8), 500 ml of the crude extract and 25 mM sodium borate buffer was measured spectrophotometrically at 290 nm (Hitachi U 2000, Japan).…”
Section: Biochemical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenate was centrifuged at 20,000 g for 20 min at 48C in a refrigerated high-speed centrifuge (Hitachi, Japan). PAL activity in the supernatant of the cell free extracts was assayed as described by Geetha et al (2005). The reaction mixture (3 ml) consisted of 50 mM L-phenylalanine in 100 mM sodium borate buffer (pH 8.8), 500 ml of the crude extract and 25 mM sodium borate buffer was measured spectrophotometrically at 290 nm (Hitachi U 2000, Japan).…”
Section: Biochemical Studiesmentioning
confidence: 99%
“…Furthermore, the involvement of various defense enzymes such as peroxidase, phenylalanine ammonia lyase, and polyphenol oxidase have also been studied (Shivakumar et al 2003;Geetha et al 2005;Niranjan Raj et al 2006). However, there are very limited reports on the use of plant extracts for plant disease management.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan of poly-(1Á4)-b-D-glucosamine is known to induce systemic resistance in PM and protects through activation of defense responses (Manjunatha et al 2008(Manjunatha et al , 2009. It has also been demonstrated that defense-related enzymes have been involved in resistance against PMÁDM interaction and that these enzymes act as biochemical markers for induction of disease resistance (Shivakumar et al 2003;Geetha et al 2005;Sudisha et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…All the measurements were taken in both sunexposed and shaded sites. Epidermal polyphenols (EPhen) were optically estimated in situ using the portable leaf-clip device Dualex (Force-A, Orsay, France) that determines the epidermal absorbance in the UV-A, mainly due to flavonoids, by comparing the chlorophyll fluorescence (ChlF) signals at two different excitation wavelengths (375 and 650 nm) (Goulas et al, 2004;Cartelat et al, 2005). The EPhen content was expressed in absorbance units as indicated by the Dualex.…”
Section: Methodsmentioning
confidence: 99%
“…New indications of the role of flavonoid metabolism are emerging in resistance to downy mildew in other pathosystems, such as the monocot Pennisetum glaucum against Sclerospora graminicola (Geetha et al, 2005;Niranjan Raj et al, 2006). There was an increase in infection caused by different pathogens with several species under shade environments (Pennypacker, 2000;Roberts & Paul, 2006).…”
Section: Introductionmentioning
confidence: 99%